Efektivitas Permainan Puzzle dan Balok terhadap Peningkatan Keterampilan Sosial Emosional Anak Usia Dini di PAUD Mbah Ceria Medan Pada Masa Pandemi Covid-19 - Yusmiati Yusmiati; Amanah Surbakti; Masganti Masganti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the effectiveness and differences of puzzle and block games on improving children's socio-emotional at PAUD Mbah Ceria Medan during the Covid-19 Pandemic. This type of research is a quasi-experimental design using pretest - posttest. The research population was all of Mbah Ceria's PAUD students, totaling 75 children. The sampling technique used purposive sampling with a total sample of 22 children. The data collection method used a child's social emotional checklist sheet with the scale used was the rating scale. Analysis of research data shows that (1) Puzzle games are effective in increasing children's socio-emotional at PAUD Mbah Ceria Medan during the COVID-19 Pandemic with an N-Gain Score of 0.4709; the effective contribution of X1 to Y is 47.1% (2) The game of blocks is effective for improving the social and emotional of children at PAUD Mbah Ceria Medan during the COVID-19 Pandemic with an N – Gain Score of 0.4800; the effective contribution of X2 to Y is 48.0% (3) There is a difference in the effectiveness of Puzzle and Block Games on children's socio-emotional improvement in PAUD Mbah Ceria Medan during the COVID-19 Pandemic, where the difference in the N - Gain Score of Puzzles and Blocks is 0.0091.